1997
DOI: 10.1095/biolreprod56.5.1351
|View full text |Cite
|
Sign up to set email alerts
|

Decidua-Associated Suppressor Cells in Abortion-Prone DBA/2-Mated CBA/J Mice that Release Bioactive Transforming Growth Factor β2-related Immunosuppressive Molecules Express a Bone Marrow-Derived Natural Suppressor Cell Marker and γδ8 T-Cell Receptor1

Abstract: The decidua of allopregnant mice contains a novel population of Thy1 Lyt1 CD4 CD8 asialoGM1- non-B small lymphocytic suppressor cells that release transforming growth factor (TGF) SS2-related suppressor molecules. The "null" phenotype of this cell population is similar to some bone marrow-derived natural suppressor cell (NSC) populations, and the latter may release TGF(beta)s. We now report that the TGF beta2-producing suppressor cells in the uterine decidua of DBA/2-mated CBA/J female mice-linked to preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Nevertheless, successful pregnancy, which is reliant on progesterone in either species, is also known to be dependent upon appropriate expression of decidual TGF-β2 in mice [46][47][48]. Therefore, in the current study, we further explored whether the reduced PR expression observed in adult mice uteri subsequent to in vivo TCDD exposure impacted TGF-β2 expression in response to either estradiol alone or estradiol plus progesterone.…”
Section: Endometrial Tgf-β2 Expression In Adult Mice Subsequent To Dementioning
confidence: 99%
“…Nevertheless, successful pregnancy, which is reliant on progesterone in either species, is also known to be dependent upon appropriate expression of decidual TGF-β2 in mice [46][47][48]. Therefore, in the current study, we further explored whether the reduced PR expression observed in adult mice uteri subsequent to in vivo TCDD exposure impacted TGF-β2 expression in response to either estradiol alone or estradiol plus progesterone.…”
Section: Endometrial Tgf-β2 Expression In Adult Mice Subsequent To Dementioning
confidence: 99%
“…The reasons why lymphocytes are elevated in the pregnant spleen may be manifold. For example, natural suppressor cells, identifi ed as T lineage lymphocytes, during pregnancy, produce transforming growth factor ␤ 2 , a cytokine which inhibits both mono- cyte/macrophage, and NK cells, both of which are abortogenic [39][40][41][42] . Secondly, interleukin-10, another T-lineage lymphocyte product, is a powerful downregulator of infl ammatory cytokines and is associated with successful human pregnancy [43] , and is elevated in successful murine pregnancy, while absence of interleukin-10 is associated with fetal demise [43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, progesterone may act to inhibit graft rejection, at least in part, by inducing the presence of suppressive γδ T cells in the endometrium. This hypothesis is suggested by the fact that progesterone tended to increase the number of γδ T cells in the glandular epithelium and suppressive γδ T cells that secrete transforming-growth factor are present in the mouse uterus during pregnancy [14, 15]. In addition, there is evidence for the existence of γδ T cells that promote graft survival [24].…”
Section: Discussionmentioning
confidence: 99%
“…These three markers, one or more of which can be present on an individual lymphocyte, are: CD45R, which identifies naïve T cells; CD8, which typically represent cytotoxic T cells, and the γδ T-cell receptor, which marks a major fraction of endometrial T cells during late pregnancy in sheep [13]. Lymphocytes of the γδ T-cell lineage have been implicated as playing an immunosuppressive role during pregnancy in mice [14, 15]. …”
Section: Introductionmentioning
confidence: 99%